Efficiency of a novel thermosensitive enema in situ hydrogel carrying Periplaneta americana extracts for the treatment of ulcerative colitis - Wu, Ming; Ding, Hui; Tang, Xiao; Chen, Jiayi; Zhang, Meng; Yang, Ziqiong; Du, Qian; Wang, Jun (Frontiers in Pharmacology, 2023)
Objective: The aim of this study was to develop a thermosensitive in situ gel (TISG) as an effective rectal delivery platform for delivering Periplaneta Americana extracts (PA) to alleviate ulcerative colitis (UC) and explore the underlying molecular mechanism. Materials and Methods: Thermosensitive (poloxamer 407) and adhesive polymers (carboxymethyl chitosan grafted by chondroitin sulfate, CCMTS) were used to construct the in situ gel. CCMTS and Aldehyde Poloxamer 407 (P407-CHO) were synthesized and chemically cross-linked by Schiff base reaction to formulate TISG, which carried PA (PA/CCMTS-P). The cytotoxicity and cellular uptake of CCMTS-P were investigated in lipopolysaccharide (LPS) -induced macrophages by CCK-8 assay. The anti-inflammatory effects of PA/CCMTS-P were studied in LPS-induced RAW264.7 cells and dextran sulfate sodium (DSS)-induced UC mouse models. In addition, the ability of PA/CCMTS-P to restore the intestinal mucosal barrier after rectal administration was evaluated by immunohistochemical analysis (IHC). Results: PA/CCMTS-P was prepared and characterized as gel with a phase-transition temperature of 32.9℃. The results of the in vitro experiments indicated that the hydrogels promoted the cellular uptake of PA without causing any toxicity as compared to the free gel. PA/CCMTS-P showed superior anti-inflammatory activity both in vitro and in vivo, which restored the damaged intestinal mucosal barrier associated by inhibiting necroptosis in DSS-induced UC models. Conclusion: The findings from our study show that the rectal administration of PA/CCMTS-P holds a promising potential for the treatment of UC.